2020
DOI: 10.1039/d0cc04509h
|View full text |Cite
|
Sign up to set email alerts
|

Is electron ping-pong limiting the catalytic hydrogen evolution activity in covalent photosensitizer–polyoxometalate dyads?

Abstract: Understanding the limitations of catalytic processes enables the design of optimized catalysts. Here, femtosecond transient absorption spectroelectrochemistry is used to explore the photophysics of polyoxometalate-based covalent photosensitizer-hydrogen evolution catalyst dyads....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The team demonstrated that variation of the central heterometal (Fe 3+ , Co 3+ , Mn 3+ ) of the Anderson anion can be used to tune the light‐driven hydrogen evolution of these systems. Further, detailed time‐resolved optical spectroscopy and spectro‐electrochemistry demonstrated the charge‐separation pathways [28] and identified limiting processes for the hydrogen evolution catalysis [29] …”
Section: Introductionmentioning
confidence: 98%
“…The team demonstrated that variation of the central heterometal (Fe 3+ , Co 3+ , Mn 3+ ) of the Anderson anion can be used to tune the light‐driven hydrogen evolution of these systems. Further, detailed time‐resolved optical spectroscopy and spectro‐electrochemistry demonstrated the charge‐separation pathways [28] and identified limiting processes for the hydrogen evolution catalysis [29] …”
Section: Introductionmentioning
confidence: 98%
“…Thus, light-driven catalytic studies were performed in waterfree, de-aerated DMF solutions containing the respective catalyst POM-PtX (12.5 μM), the photosensitizer PS (125 μM) and triethyl amine/acetic acid (TEA (1.0 M)/HAc (0.2 M)) as sacrificial proton/electron donors; this experimental setup has been adapted from earlier POM-based HER studies. [48,[50][51][52] The samples were irradiated under an Ar atmosphere using monochromatic LEDs (λ max = 470 nm, P ~40 mW cm À 2 ) at 25 °C. Hydrogen evolution was quantified by calibrated gas chromatography.…”
Section: Light-driven Hydrogen Evolutionmentioning
confidence: 99%
“…PS was chosen due to its cationic charge, and the literature-known ability for light-driven electron transfer to POMs. 25,44 In addition, (spectro-)electrochemical analyses of both POM-PtX species showed, that at least two electron transfers from the photoreduced PS (E1/2 ca. -1.8 V vs. Fc + /Fc) 45 to POM-PtX is thermodynamically possible, as POM-PtX shows two redox-couples at potentials more positive than -1.8 V (see SI, Table S2, Figures S3, S4).…”
Section: Light-driven Hydrogen Evolutionmentioning
confidence: 99%
“…Thus, light-driven catalytic studies were performed in water-free, de-aerated DMF solutions containing the respective catalyst POM-PtX (12.5 µM), the photosensitizer PS (125 M) and triethyl amine/acetic acid (TEA (1.0 M) / HAc (0.2 M)) as sacrificial proton/electron donors; this experimental setup has been adapted from earlier POM-based HER studies. 44,[46][47][48] The samples were irradiated under an Ar atmosphere using monochromatic LEDs (λmax = 470 nm, P ~ 40 mW cm -2 ) at 25°C. Hydrogen evolution was quantified by calibrated gas chromatography.…”
Section: Light-driven Hydrogen Evolutionmentioning
confidence: 99%